MONITORING KEAKTIFAN TENAGA PENGAJAR BIDANG PENDIDIKAN PP. SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Akhlis Munazilin; Ahmad Homaidi; Abd. Ghofur (Jurnal Ilmiah Informatika, 2017)
This research was conducted to overcome the problems that has complained by the higher education sector in controlling to the schools under the auspices of SalafiyahSyafi’iyah Boarding School SukorejoSitubondo Education sector. To overcome the problem, one of the solution is to make an information media (software) that can see the condition of learning and teaching process in every single school, so to be able to know the real-time information education sector does not need to go around the schools, by connecting the device to the information internet which expected to be viewable through the work desk. System Developing method that used in this research is waterfall method. The usage of this method is choosen because the reach of the research project is not too large (small). Software to be created is Server-side with PHP programming language and using MySQL database. With this system, is expected to overcome the problem that has complained by the highest education sector. So, the information obtained is accurate as needed. The result of this information media production is “Monitoring Information System tecaher activity of salafiyahsyafiiyahsukorejositubondoislamic boarding school higher education sector” which can report the class atmosphere of every single school in real-time based on the schedule of learning and teaching activity.